Donor-Recipient Mismatch in Lung Transplantation: The Role of Graft Sizing in Clinical Outcomes - Chiara Catelli; Chiara Catelli; Miriana D’Alessandro; Andrea Lloret Madrid; Antonella Fossi; Federico Franchi; Federico Franchi; David Bennett; Piero Paladini; Piero Paladini; Elena Bargagli; Elena Bargagli; et al. (Transplant International)
Lung transplantation is a life-saving procedure for end-stage lung diseases. Size matching is critical in the donor-recipient selection process. This retrospective study analyzed 146 patients who underwent lung transplantation between 2013 and 2023. Patients who required graft resizing were assigned to the sizing group (S), non-resizing cases to the non-sizing group (NS). The primary goal was to identify predictive factors for graft resizing. Secondary endpoints included ischemia time, ventilation time, primary graft dysfunction (PGD) and hospital stay. The S group was further stratified on baseline parameters to assess differences in outcomes. Recipient height and single transplants were higher in the NS group. Donor-recipient height ratio was the only predictor for resizing (p = 0.02). Postoperative outcomes and overall survival were similar between the groups. In Group S, male patients showed higher rates of acute kidney injury (AKI) and chronic rejection, the former being associated also with anatomical resections; patients older than 50 experienced higher rates of PGD. Graft resizing is a feasible strategy for addressing size mismatch, but it is associated with increased risks of PGD and AKI, particularly in older male recipients and those undergoing anatomical resections. These findings highlight the importance of careful preoperative donor-recipient size matching.